2009
DOI: 10.1111/j.1532-5415.2009.02526.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dysphasia and Dysphagia on Inpatient Mortality and Hospital Length of Stay: A Database Study

Abstract: Patients with dysphagia have worse outcome in terms of inpatient mortality and length of hospital stay than those with dysphasia. When both conditions are present, the presence of dysphagia appears to determine the likelihood of poor outcome. Whether this effect is related just to stroke severity or results from problems related directly to dysphagia is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
94
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 23 publications
(32 reference statements)
8
94
3
2
Order By: Relevance
“…We found that OD is a risk factor for mortality but discerned no difference in length of hospital stay. A recent study observed that in patients admitted for stroke, OD prolongs length of stay by almost 40% and is associated with 30.5% hospital mortality (vs. 2.8% in patients with non-OD) [28]. The difference between the results of that study and our own results might be related to the low prevalence of stroke patients in our care unit.…”
Section: Discussioncontrasting
confidence: 56%
“…We found that OD is a risk factor for mortality but discerned no difference in length of hospital stay. A recent study observed that in patients admitted for stroke, OD prolongs length of stay by almost 40% and is associated with 30.5% hospital mortality (vs. 2.8% in patients with non-OD) [28]. The difference between the results of that study and our own results might be related to the low prevalence of stroke patients in our care unit.…”
Section: Discussioncontrasting
confidence: 56%
“…2 Current rehabilitative strategies, including behavioral therapies have limited evidence base. 3 However, with recent developments in our understanding of the role of neuroplasticity and cortical reorganization in swallowing recovery, [4][5][6] there is now increasing interest that neurostimulation techniques can drive this natural recovery process.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] In contrast to behavioral swallowing treatments, PES appears to promote functional benefit through a central nonbiomechanical mechanism, such that dysphagia is improved regardless of physiological deficit. Furthermore, the optimal stimulation parameters (5-Hz frequency, 10 minutes duration, and 75% of maximum tolerated intensity) 8 have been shown to reverse the neurophysiological and behavioral effects of experimental brain 1 University of Manchester, Salford, UK 2 Salford Royal Foundation Trust, Salford, UK lesions, 9,13 and a dose-response study provided an optimal regimen in dysphagic stroke patients-once-daily stimulation for 3 days. 9 Moreover, in randomized clinical studies, PES improved swallowing within an hour poststimulation in both acute 8 and chronic 11 dysphagic stroke patients, as measured with videofluoroscopy (VFS).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Laboratory evidence of OPD can assist prevention of serious consequences in OPD patients. Several studies reported the utility of high-resolution impedance manometry (HRIM) for evaluation of oropharyngeal dysphagia.…”
Section: Introductionmentioning
confidence: 99%